FRI0061 Remission after one year follow up of the improved-study, a randomized clinical trial aiming at remission in patients with early rheumatoid and undifferentiated arthritis. (23rd January 2014) - Heimans, L.; Wevers-de Boer, K.V.C.; Visser, K.; Ronday, H.K.; Oosterhout, M.; Harbers, J.B.; Peeters, A.J.; Westedt, M.L.; de Buck, P.D.; de Sonnaville, P.B.; Grillet, B.A.; Huizinga, T.W.; et al.
Abstract : Objectives: To evaluate the 1 year clinical outcomes of remission steered therapy in early arthritis, initially with methotrexate (MTX) and a tapered high dose of prednisone, in case of remission followed by tapering medication to zero, in case of no remission followed by randomization to two combination therapy strategies. Methods: IMPROVED is a multicenter clinical trial in 479 patients with early (symptoms <2 years) rheumatoid arthritis (RA 2010 criteria) and 131 patients with undifferentiated arthritis (UA) with a baseline Disease Activity Score (DAS) ≥1.6. All patients started with MTX 25mg/wk and prednisone 60mg/day tapered in 7 weeks to 7.5 mg/day. Patients in early remission (DAS <1.6 at t=4 months) tapered prednisone to zero and when still in remission at t=8 months, also tapered MTX to zero. Patients not in early remission were randomized either to a combination of MTX 25 mg/wk, hydroxychloroquine (HCQ) 400mg/day, sulphasalazine 2000mg/day (SSZ) and prednisone 7.5 mg/day (arm 1) or to adalimumab (ADA) 40mg/2weeks with MTX 25mg/wk (arm 2). If not in remission at t=8 months, patients in arm 1 switched to ADA+MTX and patients in arm 2 increased ADA to 40mg/week. Proportions of remission after one year follow up were compared between the different treatment strategies and between RA and UA patients. Results: After 4 months 375/610 (61%) patients achieved early remission (mean DAS (SD) 0.94 (0.36)) and 221/610 (36%) did not (mean DAS (SD) 2.45 (0.65), p<0.001). 161/610 patients (26%) were randomized, 83 to arm 1 and 78 to arm 2. In 66/610 (11%) patients the appropriate treatment step was not taken for various reasons. 12 patients were lost to follow up at t=4 months and 34 at t=1 year. At t=4 months, 361/375 (96%) patients in early remission started tapering prednisone. At t=8 months 257/375 (68%) were still in remission on MTX monotherapy and 200/375 (53%) tapered MTX to zero. At t=1 year, 255/375 (68%) were in remission, 135/375 (36%) were in drug free remission. At t=8 months 50/83 (60%) patients in arm 1 did not achieve remission and 31/83 (37%) switched to ADA+MTX. 47/78 (60%) patients in arm 2 did not achieve remission and 27/78 (35%) increased ADA. At t=1 year 21/83 (25%) patients in arm 1 and 32/78 (41%) in arm 2 were in remission (p<0.001). At t=1 year, 326/610 (53%) of the total study population were in remission: 252/479 (53%) RA patients and 70/131 (53%) UA patients. Conclusions: In patients with early RA or UA, early remission was achieved in 61% after initial treatment with MTX and a tapered high dose of prednisone. After one year of tapering treatment, 68% of those were still in remission and 36% in drug free remission. For those not in early remission, treatment with adalimumab resulted in more remission than a combination of DMARDs with low dose prednisone. Of the total study population 53% were in remission after one year, without a significant difference between early RA and UA patients. Disclosure of Interest: L. Heimans: None Declared, K. Wevers-de Boer Grant/Research support from: Abbott, K. Visser: None Declared, H. Ronday: None Declared, M. Oosterhout: None Declared, J. Harbers: None Declared, A. Peeters: None Declared, M. Westedt: None Declared, P. de Buck: None Declared, P. de Sonnaville: None Declared, B. Grillet: None Declared, T. Huizinga: None Declared, C. Allaart: None Declared